Analisis Butir Soal Tipe Multiple Choices Questions (MCQ) pada Ujian Akhir Semester Ganjil Mata Pelajaran Sosiologi Kelas XII SMA - Rahmat Fajar; Junaidi Junaidi (Jurnal Sikola: Jurnal Kajian Pendidikan dan Pembelajaran, 2022)
This study aims to determine the quality of the Odd Semester Final Examination Questions for Class XII Sociology Subjects at SMA Negeri 2 Padang Panjang in the 2021/2022 academic year in terms of analysis: 1) content and empirical validity, 2) reliability, 3) distinguishing characteristics, 4) difficulty level. And 5) distracting qualities. This research is a descriptive study using a quantitative approach because all the data or information obtained is manifested as numbers. The research subjects were students of class XII SMA Negeri 2 Padang Panjang, with a total population of 163 students. Data collection techniques were carried out using the documentation method to obtain data on questions, answer keys, and student test results. Based on the results of data analysis, the results of a review of aspects are obtained: 1) The validity of the content of the questions has a high category material aspect, a high category construction aspect, and a high category linguistic aspect. 2) Empirical validity, there are 7 items valid questions (17.5%) and 33 items (82.5%). 3) In terms of reliability, the question has low reliability of 0.19. 4) Discriminatory power, questions with less discriminating power 23 items (57.5%), questions with sufficient discriminating power 14 items (35%), good discriminating power three items (7.5%). 5) Difficulty level, 16 items (40%) are classified as easy, 12 items (30%) are classified as moderate, and 12 items are items (30%) ) are difficult. 6) The effectiveness of distractors, 29 items (72.5%) are eligible, and 11 items (27.5%) are not eligible. Thus it can be concluded that the quality of the items tested is not good.